Pengaruh Kualitas Produk, Citra Merek, dan Harga terhadap Keputusan Pembelian Ponds Flawless White - Indah Siti Mahmudah; Monika Tiarawati (BISMA (Bisnis dan Manajemen), 2018)
The success of this product is Indicated by the results of theTop Brand in 2011-2012 Pond's still ranked first with a larger percentage. With good quality and reliable brand image and an affordable price, pond's will always be embedded inside consumers. The population used is all consumers who are involved in purchasing decisions pond's flawless white as much as 110. Withdrawal method and the sampling was purposive sampling technique used is linear to influence the magnitude of the effect. These results can be seen from the adjusted R Square of 0.604 means that there are variables influence product quality, brand image, and price on purchase decisions by 60.4% while the rest is influenced by other variables outside of this study was 39.6%. In this study the variable quality of the product is the dominant variable.